A Suitable LDR Image from HDR by CIELAB Based Tone-Mapping Algorithm - Patel, Arpna; Dubey, Ratnesh; Richhariya, Vineet (International Journal of Computer Sciences and Engineering, 2025)
This paper presents an analysis of the CIELAB color feature based tone mapping technique. After analysis of these techniques we had concluded that saliency based tone mapping algorithm is not computationally efficient as good as the proposed methodology. There is different Salience-based Tone mapping methods for High dynamic range images that have the halo artifacts significantly reduced. The visual quality of tone-mapped image, especially based on salient regions, is enhanced by the saliency-aware weighting. Experimental results show that the proposed method produce good results on a variety of high dynamic range images as saliency-aware technique. The proposed method is more computational efficient and the visual quality of the proposed method is also improved as of saliency based tone mapping.